Enhancing Data Protection in Banking: Implementation and Evaluation of an AI-Driven System - Sugianto, Sugianto; Soetomo, Mohammad A; Ipung, Heru (Syntax Corporation, 2025)
This research aims to implement an AI-driven system for managing Records of Processing Activities (RoPA) and Data Protection Impact Assessments (DPIA) at Bank XYZ to comply with Indonesia’s Personal Data Protection Law (PDPL). The research uses a qualitative approach, incorporating case studies and interviews to investigate the AI system’s impact on improving compliance, efficiency, and data security within the banking sector. Initial results show significant improvements in the accuracy and speed of processing personal data protection documents. The AI system simplifies the management of RoPA and DPIA and promotes a robust compliance environment by adhering to national and international data protection standards. It is recommended to continually advance AI and provide ongoing training to address emerging data security and privacy challenges.